Milk Production and Fatty Acids Balance of Dairy Goat Fed Diet with Fermented Durio zibethinus Peel - Sulistyowati, Endang; Badarina, Irma; Mujiharjo, Sigit (Universitas Halu Oleo, 2021)
ABSTRACTThe by-product of Durio fruit is huge potential biomass to be utilized as a feed ingredient. However, it needs to be treated physically and biologically such as by fermentation. The objectives of this study were to evaluate nutrient contents, nutrient intakes, nutrient digestibility, milk yield, milk composition, and fatty acid contents in concentrate, milk, and feces of dairy goat fed the diet with a concentrate containing fermented Durio peel flour. The backlogs containing a mixture of Durio peel flour, rice bran, and CaCO3 were fermented with Pleurotus ostreatus for two weeks, air dried, then were ready to be formulated in concentrate. Treatments were FDC 0: basal diet of 55.7% tofu- by-product + 44.3% composite forage; FDC 5: basal diet + Concentrate with 5% fermented Durio peel +25% rice bran; FDC 10: basal diet + Concentrate with 10% fermented Durio peel +20% rice bran; FDC 20: basal diet + Concentrate with 20% fermented Durio peel + 10 rice bran. The experimental design used was a completely randomized design in 4 x 4, 4 treatments, and 4 replications in 40 days. Therefore, there were 16 lactating Nubian crossed goats as experimental units. Results showed there was found that the 5% fermented Durio peel flour in concentrate showed several consistency in some quality. Those were high in crude protein, ether extract, dry matter intake, gross energy, digestibility of nutrients (dry matter, organic matter, ether extract, crude protein, crude fiber, N-free extract, gross energy), milk yield, ECM, MCFA, LCFA, PUFA in milk, C<16, C>16, unsaturated, a total fatty acid in concentrates, milk, and feces. There were low SCC in milk and low n-6/n-3 in milk that were expected. Therefore, the 5% fermented Durio peel flour and 25% of rice bran in concentrate was considered optimal for lactating dairy goat.Keywords: balance, D. zibethinus, fatty acid, fermented